|Motivations for Admission of Pedagogy Students: Case of a University in Northern Chile - Álvarez Durán, Enmanuel (2024)
This research seeks to present the main motivations of pedagogy students at a university in northern Chile, between the years 2016, 2018, and 2022. The researchers employed a quantitative paradigm with a descriptive scope; likewise, they used the case study as a reference as a methodology for analyzing and justifying the data. For its part, the data collection instrument consists of an adaptation of the original applied in 2007, which was validated by a panel of experts. The configuration of the instrument determines the main motivations for pedagogy studies and investigates others not previously collected. Its application was carried out in a total of 7 different pedagogies, with the participation of more than 80% of the students of each major. Regarding the characterization of the sample, the female gender stood out when entering pedagogy, as well as students who live within the same region of the institution and with scores over 500 PSU points (University Selection Test); this sets up the first-year student profile. Furthermore, the results show a clear trend in the three years of its application, highlighting: The taste for the speciality of my career, followed by I liked the idea of working with children and/or young people, I liked the teaching and I wanted to help others through the exercise of teaching. Because these categories are related to other studies from different years and contexts, but on the same topic, it can be stated that there are common motivations for the interest in teaching. Having this information offers an opportunity for the institution to carry out student retention actions aimed at motivating and attracting future teachers. Likewise, the topic can be delved into by considering other variables, such as whether there is variation in interest according to the disciplinary area, the different years of the degree, or the professional career.